THE The Effect of Employability and Work Motivation on the Productivity of Workers with Disabilities at PT. Wangta Agung - Lubis, Dina Mariana Uli; Asfan, Muhammad; Nurwantoro, Nurwantoro; Pujiyanto, Risang (Neolectura, 2025)
This research aims to determine the influence of work ability and work motivation on the productivity of workers with disabilities at PT. Wangta Agung. As a form of inclusion and equal employment opportunities, PT Wangta Agung employs workers with disabilities who are usually not considered enough and do not get the same opportunities as other workers. Data analysis was carried out using multiple line regression. Based on research, it can be concluded that work ability and work motivation simultaneously have a positive and significant effect on the productivity of workers with disabilities at PT. Wangta Agung. Likewise, partial testing shows that both work ability and work motivation have a significant influence on the productivity of workers with disabilities at PT. Wangta Agung. Based on this, companies need to consider improving the work ability of their workforce and motivating them so that it has a positive impact on increasing productivity in order to achieve company goals.